Chapter What We Learned from Cavitation Bubbles in Microgravity - Farhat, Mohamed (InTechOpen, 2020)
The present chapter is about the Flash and Splash project, which is dedicated to the study of bubble dynamics in microgravity. The story of this project started in 2004 with a simple curiosity on how a cavitation bubble may behave within a water drop and evolved into an outstanding, internationally renowned science project as well as a wonderful human adventure. So far, we have participated in nine European Space Agency (ESA) parabolic flight campaigns (PFC) and made a significant progress in understanding the cavitation phenomenon. First, we investigated the dynamics of a cavitation bubble within a water drop and learned how the collapse may lead to the formation of a double jet. We discovered the formation of secondary cavitation due to the confinement of shockwaves within the drop. We used this result to propose a new path for erosion due to a high-speed impact of water drops on a solid surface. Then, we addressed the effect of gravity on bubble dynamics and came up with a unified framework to explain and predict key phenomena, such as microjets, shockwaves and luminescence. Parabolic flights gave us the unique opportunity to modulate the gravity-induced pressure gradient, which is crucial for the fate of a collapsing bubble.